The Impact of Related Party Transactions on Company Performance Manufacturing Companies Listed on the Indonesia Stock Exchange - Agung Darmawansyah; Luke Suciati Amna (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to determine the effect of related party transactions (RPTs) on the performance of manufacturing companies listed on the Indonesia Stock Exchange during the period 2020-2021. This highlights the ongoing concerns over the potential for fraud associated with RPTs, which can create significant agency problems, particularly between controlling shareholders and minority shareholders. This study confirms that RPTs can have both positive and negative impacts on economic performance, depending on how they are managed. While strong indications emerge from the literature that RPTs enhance firm value through effective resource allocation, there are important risks such as tunneling practices that can exploit minority shareholders. This methodology employs quantitative analysis using multiple regression on data from 30 selected manufacturing companies. Key findings reveal a significant positive relationship between RPTs and return on assets (ROA), confirming that related party transactions can generate financial benefits by maximizing profits while minimizing transaction costs. In addition, firm size and leverage are identified as crucial factors influencing performance, indicating that larger firms with substantial asset bases generally achieve better profitability metrics. Overall, this study underlines the complexity of related party dynamics within the corporate governance framework and suggests regulatory measures to protect the interests of minority shareholders while leveraging RPTs for corporate growth.